2014
DOI: 10.1111/jre.12172
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of high‐sensitivity C‐reactive protein and lipid levels in healthy adults and patients with coronary artery disease, with and without periodontitis – a cross‐sectional study

Abstract: A persistent infection, such as chronic periodontitis, may influence changes in the systemic levels of HsCRP, LDL and HDL, which potentially have an impact on inflammation-associated atherosclerotic processes, such as CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 88 publications
2
20
0
1
Order By: Relevance
“…This condition leads to lipid metabolism disorders that are characterized by an increase in serum Tcho and LDL levels . In this context, our findings support the view that periodontitis may increase the risk of CVD by affecting lipid profiles associated with an increase in CRP levels . Furthermore, it has been demonstrated that hyperlipidemia increases susceptibility to infection by negatively affecting immune system cells .…”
Section: Discussionsupporting
confidence: 87%
“…This condition leads to lipid metabolism disorders that are characterized by an increase in serum Tcho and LDL levels . In this context, our findings support the view that periodontitis may increase the risk of CVD by affecting lipid profiles associated with an increase in CRP levels . Furthermore, it has been demonstrated that hyperlipidemia increases susceptibility to infection by negatively affecting immune system cells .…”
Section: Discussionsupporting
confidence: 87%
“…Many authors have demonstrated that CRP concentration is higher in patients with periodontitis and CVD compared to patients with only one of these two disorders [3,16,20,23,24]. This was also confirmed in a meta-analysis by Paraskevas et al [25].…”
Section: Discussionmentioning
confidence: 77%
“…These outcomes show that both periodontal tissue breakdown (PD) and level of inflammation (bPP) impinge on the lipid serum level. The results of scientific research on LDL-C concentration in the blood of patients with CVD depending on the state of periodontal tissues are ambiguous [16,17]. However, the majority of reports on patients without cardiovascular burden indicate an impact of periodontitis on lipid disorders expressed by elevated levels of LDL-C, TC and TG, and a reduced level of HDL-C [3,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The high consumption of soft drinks is associated with increased triglycerides, reduced HDL levels and increased C‐reactive protein, which are metabolic and inflammatory disorders present in periodontal disease …”
Section: Discussionmentioning
confidence: 99%
“…Periodontal diseases have also been associated with reduced HDL, high triglycerides, hypertension, type 2 diabetes, visceral obesity, metabolic syndrome, and cardiovascular disease …”
Section: Introductionmentioning
confidence: 99%